Instrumen Discharge Planning Berbasis Patient Family Centered Care - Uut, Paskalia; Fitryasari, Rizki; Armini, Ni Ketut Alit (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to develop a discharge planning instrument through an inpatient family centered care approach, to improve service quality. The method used was systematic review, a systematic search through the Scopus, Science Direct, and Pub Med databases published between 2018-2023. The results showed that discharge planning based on patient family centered care helps prepare patients and families for home care, increase knowledge and skills, and collaborate with other health workers. The conclusion of this study is that discharge planning has an influence on the success of patient care after being at home. The implementation of discharge planning is important in preparing patients and families with education by nurses related to the disease and patient care so as to increase knowledge and skills for home care. Improved quality of service at home and patient and family satisfaction. Keywords: Discharge Planning, Instrument Development, PFCC, Hospitalization, Hospital.